Proton Pump Inhibitors in the Elderly Hospitalized Patient: Evaluating Appropriate Use and Deprescribing. (April 2020) - Mehta, Nishila; Martinez Guasch, Fernando; Kamen, Corey; Shah, Sumesh; Burry, Lisa D.; Soong, Christine; Mehta, Sangeeta
Background: Proton pump inhibitors (PPIs) are often prescribed for elderly patients without appropriate indication, or for longer durations than recommended.Objective: To review appropriateness of PPI use prior to and in hospital, and deprescribing rates across different hospital units.Methods: Retrospective analysis of patients ≥65 years admitted to 5 acute care units: intensive care unit, acute care for elderly, orthopedics, surgery, and medicine. Patients who were "non-naive" (prehospital PPI use) or "naive" (new PPI initiated in hospital) users were included. For both groups, demographics, reason for admission, length of stay, comorbidities, name and number of home medications, PPI name, dose and indication, and PPI discharge instructions were collected. For naive patients, duration of in-hospital use and prescriber specialty was recorded.Results: Among non-naive patients (n = 377), for 37 patients (10%), the indication for a PPI was not appropriate, and for 92 patients (24%), the indication was unclear. Most patients had their home PPI continued while in hospital (87%) and at discharge (90%). Among naive (n = 93) patients, for 8 patients (9%), the indication for a PPI was not appropriate, and for 25 (27%) patients, the indication was unclear. PPI was prescribed to only 16 (18%) by the gastrointestinal consult service. Most patients had their new PPI continued at discharge (74%); only 7 (9%) were discharged with a plan to reassess PPI indication.Conclusion: PPIs are infrequently deprescribed during hospital admission, despite inappropriate or unclear indications for use. Thorough medication reconciliation, documentation of PPI indication and duration, and institutional focus on deprescribing are encouraged.